IMPLEMENTATION OF RESTORATIVE JUSTICE IN THE CASE OF TRAFFIC ACCIDENTS THAT CAUSED THE DEATH OF THE VICTIM - I Made Wahyu Chandra Satriana; Ni Made Liana Dewi; Berliana Indahsari (International Journal of Education and Social Science Studies, 2026)
Highways play a crucial role in socio-economic activities; however, traffic accidents resulting in fatalities remain a significant legal and social issue. The important role of this highway is sometimes not realized by road users to obey and obey traffic on the highway, so that it can cause a problem if a traffic accident causes the victim to die. The study aims to examine the implementation of restorative justice in fatal traffic accident cases in the SARBAGITA region and to identify the challenges encountered. This research used empirical legal research methods or field research with an emphasis on the gap between das sein and das solen or between the aspired regulations and their practice in the field related to the problems discussed. The findings indicated that restorative justice is implemented through formal agreements, including peace request letters, settlement agreements, and dispute resolution statements. Recommendation for special case titles that agree to settlement with restorative justice. Investigators facilitate the settlement process and may issue a Warrant for Termination of Investigation based on restorative justice considerations.. The obstacles faced include that there are still people as victims' families who have not been able to accept the loss of their family members, the costs that must be incurred by the perpetrator and the perpetrator's family are too high (expensive) and there is a change of mind in resolving this accident case.